Penguatan Pengawasan Partisipatif Pemilih Perempuan Kelurahan Jayengan Kecamatan Serengan Kota Surakarta - Abbas, Ngatmin; Mulyanto Abdullah Khoir; Alfian Eko Rochmawan; Nurul Hidayah; Nurul Fathimah; Muh. Iqbal (Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2024)
This research aims to explore the role and impact of strengthening participatory supervision of female voters in the 2024 Election in Jayengan Sub-district, Surakarta City. The method employed is a qualitative approach through community engagement, focusing on collaboration between the Mamba'ul Ulum Islamic Institute Surakarta and local election supervisory agencies. The findings indicate an improvement in the understanding and participation of female voters in election supervision, with indications of a positive trend towards transparency and integrity in the electoral process.